Diversity in Action: The Story of an Art Workshop for Neurodiverse Students - Ne'eman, Adi; Shalev, Ma'ayan; Fine, Ya'ara Hermelin (Autonomy and Responsibility Journal of Educational Sciences, 2022)
This paper presents the story of a unique academic course that focuses on the experience of shared learning and co-creation in a neurodiverse group of students in college. The Department of Special Education at Oranim College of Education strives to develop a humanistic approach among special education preservice teachers that accepts every person, regardless of individual characteristics. These preservice teachers learn that it is important to support all dimensions of their students’ development, addressing their diverse learning needs. Based on this vision, special education preservice teachers were offered an art workshop, in which they participate with neurodiverse students with or without intellectual disability, coming from a variety of religions—Jews, Muslims and Christians. The field of art was chosen as it provides equal opportunity of expression for participants, without requiring prior abilities or skills. This paper will present the story of this course in the eyes of both the teaching staff and participants, dealing with themes such as apart and together, communication and connection, and different perspectives.